The Science Behind Nefertiti's Beauty: A Plastic Surgeon's Analysis - Kashan Shaikh, Sadia Rasheed, Jameeat Mal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The ancient queen Nefertiti has been celebrated throughout the history as one of the most gorgeous women to have ever lived. Her striking looks have captivated people for centuries, inspiring countless works of art and even fashion trends. Nefertiti's beauty may have been enhanced further by her hairstyle, which included a long, flowing wig that draped down over her shoulders Study design: It was a randomized controlled study, conducted at Institute of Plastic and Reconstructive Surgery LUMHS Jamshoro Hyderabad for the duration of six months from September 2022 to February 2023. Material and Methods: In this anthropological study, the frontal view of the face was studied. When the lower two and three canons were measured, it was estimated that both the proportions were equal and the ratio was 1:1. The study was approved by the review and ethical board committee of the hospital. The measurement of vermillion of the upper and lower lip revealed 1:1.4 ratios. Results: In the lateral view of the face, the lower two and three canons were measured and the ratio was exactly the same as measured in the lateral view i.e. 1:1. The length of the nose and ear was almost equal i.e. 23 mm and 22 mm, respectively. Conclusion: The sculpture of Nefertiti’s bust was made three million years ago, and the difference of time period in both the events still the anthropometric parameters are quite similar in both the cases. Keywords: Beauty and Queen Nefertiti.